1988
DOI: 10.1161/01.hyp.11.2_pt_2.i153
|View full text |Cite
|
Sign up to set email alerts
|

Converting enzyme activity and angiotensin metabolism in the dog brainstem.

Abstract: SUMMARY The concentrations of angiotensin converting enzyme (ACE) activity, norepinephrine, and serotonin were measured in microdissected regions of the dog's brainstem and spinal cord. In addition, we determined the in vitro metabolism of 125 I-angiotensin I (Ang I) hi hompgenates of the same brain pnnch regions. High ACE-specific activity was found hi the monoamine-containing regions of the brainstem and in the intermediolateral column of the spinal cord. In brainstem homogenates '"I-Ang I was metabolized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
1
9

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(99 citation statements)
references
References 14 publications
3
86
1
9
Order By: Relevance
“…26 Although the present experiments did not evaluate whether local conversion of Ang II to Ang-(l-7) contributed to these responses, several observations suggest that it is unlikely. First, we have shown that in medial NTS neurons that were excited by both Ang II and Ang-(l-7), the latency to peak excitation was similar for both Ang peptides.…”
Section: Discussionmentioning
confidence: 68%
“…26 Although the present experiments did not evaluate whether local conversion of Ang II to Ang-(l-7) contributed to these responses, several observations suggest that it is unlikely. First, we have shown that in medial NTS neurons that were excited by both Ang II and Ang-(l-7), the latency to peak excitation was similar for both Ang peptides.…”
Section: Discussionmentioning
confidence: 68%
“…We also confirmed that conversion of Ang I into Ang-(l-7) is not dependent on an intermediate production of Ang II. 5 In MK-422-treated animals, inhibition of Ang II production was associated with increased levels of Ang-(l-7).…”
Section: Discussionmentioning
confidence: 97%
“…As documented above, in the past few years a large body of evidence has been accumulated suggesting a role for Ang- (1)(2)(3)(4)(5)(6)(7) in the control of hydroelectrolyte balance. However, due to several factors discussed below there is no consensus regarding the major action of Ang-(1-7) in the kidney.…”
Section: Introductionmentioning
confidence: 94%
“…Ang-(1-7) can be formed by an angiotensin converting enzyme (ACE)-independent pathway (4), and exerts important biological effects. In vitro this peptide is a potent vasopressin secretagogue (5) and possesses a potent prostaglandin-releasing activity in several cell lines (6,7).…”
Section: Introductionmentioning
confidence: 99%